Expression and Purification of BsaXI Restriction Endonuclease and Engineering New Specificity From BsaXI Specificity Subunit - Gidwani, Sonal; Heiter, Daniel; Xu, Shuang-yong (Frontiers in Microbiology, 2022)
BsaXI is a Type IIB restriction endonuclease (REase) that cleaves both sides of its recognition sequence 5’ N9 AC N5 CTCC N10 3’ (complement strand 5’ N7 GGAG N5 GT N12 3’), creating 3-base 3’ overhangs. Here we report the cloning and expression of bsaXIS and bsaXIRM genes in E. coli. BsaXI activity was successfully reconstituted by mixing the BsaXI RM fusion subunit with the BsaXI S subunit and the enzyme complex further purified by chromatography over 6 columns. As expected, the S subunit consisted of two subdomains encoding TRD1-CR1 (TRD, target recognition domain, CR, conserved region) for 5’ AC 3’, and TRD2-CR2 presumably specifying 5’ CTCC 3’. TRD1-CR1 (TRD2-CR2 deletion) or duplication of TRD1 (TRD1-CR1-TRD1-CR2) both generated a new specificity 5’ AC N5 GT 3’ when the S variants were complexed with the RM subunits. Circular permutation of TRD1 and TRD2, i.e. relocation of TRD2-CR2 to the N-terminus and TRD1-CR1 to the C-terminus generated the same specificity with the RM subunits, although some wobble cleavage was detected. The TRD2 domain in the BsaXI S subunit can be substituted by a close homolog (~59% sequence identity) and generated the same specificity. However, TRD2-CR2 domain alone failed to express in E. coli, but CR1-TRD2-CR2 protein could be expressed and purified which showed partial nicking activity with the RM subunits. This work demonstrated that like Type I restriction systems, the S subunit of a Type IIB system could also be manipulated to create new specificities. Genome mining of BsaXI TRD2 homologs in GenBank found more than 36 orphan TRD2 homologs, implying that quite a few orphan TRD2s are present in microbial genomes that may be potentially paired with other TRDs to create new restriction specificities.